The Wetlands of Northeastern Algeria (Guelma and Souk Ahras): Stakes for the Conservation of Regional Biodiversity - Salvo-Tierra, Ángel Enrique; Pereña-Ortiz, Jaime Francisco; Meddad-Hamza, Amel; Hamel, Tarek; Hammana, Chayma (MDPI, 2024)
This in-depth floristic study, conducted from 2019 to 2023 in nine temporary wetlands in the Guelma and Souk Ahras provinces, northeastern Algeria, aims to highlight the natural heritage of the region by analyzing the floristic composition in relation to environmental conditions. To achieve this goal, comprehensive inventories were conducted, revealing the presence of 317 species belonging to 64 botanical families and distributed across 204 genera. The plant diversity at each site was assessed using various biological indices, with a particular focus on the Taxonomic Distinctiveness Index (TDI) to determine the influence of environmental factors such as fires, altitude, overgrazing and agropastoral activities on biodiversity. The results highlighted the dominance of therophytes (43.22%) and the prevalence of the Mediterranean assemblage (66.25%). Moreover, 8.83% of the species were endemic, 1.89% were protected by Algerian legislation and 1.26% were listed on the IUCN Red List. The study identified Priority Conservation Zones (PCA) where the preservation of ponds, particularly MTG, TRC, BTH, and GZE, is crucial. Additionally, floristic and ecological boundaries between ponds were identified, highlighting marked biological similarities between certain pairs and notable isolations, particularly evident in the case of BTH with a significantly high TDI. These results underscore the critical importance of the studied region, emphasizing the need to integrate its floristic biodiversity into conservation efforts to enhance overall ecological integrity.
Keywords: Biodiversidad; Zonas húmedas - Argelia; Phytoecology; Temporary wetlands; Northeast Algeria; Heritage taxa; Taxonomic Distinctiveness Index; Conservation; Threat